ESTUDO DA TRANSMISSÃO NOSOCOMIAL DO VÍRUS DA HEPATITE B E AVALIAÇÃO DA SOROCONVERSÃO À VACINA RECOMBINANTE EUVAX-B NA POPULAÇÃO DE HEMODIÁLISE DE GOIÂNIA-GOIÁS - Sheila Araujo Teles (Universidade Federal de Goias, 2002)
Hemodialysis patients are at high risk to acquire hepatitis B virus (HBV) infection, and the hepatitis B vaccine is themost effective strategy for HBV prevention. In this study, during 1995 (n = 282) and 1999 (n = 536), the HBsAgpositivity was evaluated in hemodialysis patients in Goiânia-Goiás. Also, all HBsAg-reactive samples weresubmitted to HBeAg/anti-HBe and HBV DNA detection by enzyme-linked immunosorbent assay (ELISA) andpolymerase chain reaction (PCR). Moreover, HBsAg subtypes were determined by ELISA, and HBV genotypes byLine Probe Assay (LiPA) and restriction fragment length polymorphism analysis (RFLP) methods. Furthermore,hemodialysis patients (n = 42; 40 g at 0, 1, 2, and 6 month) and staff members (n = 60; 20 g at 0, 1 and 6 month)were vaccinated, and the seroconversion to recombinant Euvax-B vaccine was evaluated. In the present study, theHBsAg prevalence declined from 12% in 1995 to 5.8% in 1999 (p<0,05). Among HBsAg-positive patients (n=43),23 (53.5%) were HBeAg reactive, and 18 (41.9%) anti-HBe positive. Two individuals were negative for bothmarkers. HBV DNA was detected in all HBeAg-positive, in six anti-HBe-reactive serum samples, and in one HBeAgand anti-HBe-negative sample. In 1995, genotypes A (50%), D (46.2%) and F (3.8%), and the subtypes adw2(44.1%), ayw3 (41.2%), ayw2 (2.9%) and adw4 (2.9%) were found, and a correlation in their distribution wasobserved in the dialysis units. At the end of this investigation (1999), a shift in the endemicity of circulatinggenotypes/subtypes was noted. Samples identified as D/ayw3 (65.2%) were predominant, followed by A/adw2(30.4%) and F/adw4 (4.4%). Further, six RFLP patterns were determined: A1 (six samples), A3 (two samples), D3(10 samples), D4 (one sample), D7 (seven samples) and F1 (one sample). D3 and D7 patterns were morefrequently in Units I and II, respectively, when compared to another ones (p<0,05). Moreover, anti-HBs titres above10 UI/L were found in 89.5% and 93.3% of the patients and staff members, respectively. In despite of theimportance of dialysis environmental for HBV dissemination, the present results showed a decline in the HBVcarriers rate in the hemodialysis units in Goiânia-Goiás, and a good Euvax-B vaccine response.